The local relevance of human rights / editors, Koen De Feyter [and others]. - Feyter, K. de (Koen) (Cambridge University Press, 2011)
Do human rights offer real protection when disadvantaged groups invoke them at the local level in an attempt to improve their living conditions? If so, how can we make sure that the experiences of those invoking human rights at the local level have an impact on the further development of human rights (at national and other levels) so that the local relevance of human rights increases? Since the adoption of the Universal Declaration of Human Rights (UDHR) on 10 December 1948, numerous international documents have reaffirmed human rights as global norms. This book examines what factors determine whether appeals to human rights that emanate from the local level are successful, and whether the UDHR adequately responds to threats as currently defined by relevant groups or whether a revision of some of the ideas included in the UDHR is needed in order to increase its contemporary relevance.